Panel Analysis of Relationship between Supply Chain Strategy in Competitive Area and Economic Growth in the European Union - Abdelmajied Fathy E. Y (International Journal of Supply Chain Management, 2019)
Theoretically, the supply chain competitiveness is conclusively believed to be positively related with economic growth. While empirically, this relationship does not always hold in many countries for several reasons. In the empirical literature, the link between economic growth and competitiveness has been highly debated. Thus, the main purpose of current article is to examine the link between economic growth and competitiveness in European Union (EU-28 countries) over period from 2007 to 2017. Using Panel Models (Fixed and random effects models). In conclusion, the findings suggest that competitiveness is robustly and positively associated with real GDP per capita, if we make a policy to increase the GDP per capita, it included rise in competitiveness score for the country.